Optimalisasi Metode Edutainment Dalam Meningkatkan Minat Belajar Siswa - Nasihin, Khoirun; Bari, Abdul (Ashlach : Journal of Islamic Education, 2023)
Learning by applying the edutainment approach is an educational reform in which students are encouraged to learn actively and teachers encourage students to have experiences and conduct experiments that allow students to discover principles for themselvesThis research focuses on 1) How is the optimization of the edutainment method in increasing the learning interest of grade I elementary school students at Madrasah Salafiyah Putri, Pasuruan City? 2) What are the supporting and inhibiting factors for optimizing the edutainment method in increasing students' interest in learning at Madrasah Salafiyah Putri, Pasuruan City?This study uses a qualitative research approach. While the type of research used by researchers is descriptive. The primary data sources in this study were teachers and students of the Madrasah Salafiyah Putri Pasuruan. Data collection techniques are direct observation, structured interviews and documentation. Data analysis using data reduction, data presentation and conclusion. Checking the wetness of the data using triangulation. Optimization of the edutainment method in increasing the learning interest of elementary students at Madrasah Salafiyah Putri, Pasuruan City is a) Application of the learning method, namely active learning, b) Use of appropriate learning media.Supporting factors for optimizing the edutainment method in increasing student learning interest at Madrasah Salafiyah Putri, Pasuruan City are a) The quality of teaching staff, b) High student learning motivation. While the inhibiting factors are a) the level of students' abilities is different b) the facilities and infrastructure are inadequate.